Theology and modern physics - Hodgson, P. E. (Peter Edward) (Aldershot, Hants, England ; Burlington, VT : Ashgate Pub., 2005)
"The new discoveries in physics during the 20th century have stimulated intense debate about their relevance to age-old theological questions. Views range from those holding that modern physics provides a surer road to God than traditional religions, to those who say that physics and theology are incommensurable and so do not relate. At the very least, physics has stimulated renewed theological discussions." "In this critical introduction to the science-theology debate, Peter Hodgson draws on his experience as a physicist to present the results of modern physics and the theological implications. Written for those with little or no scientific background, Hodgson describes connections between physics, philosophy and theology and then explains Newtonian physics and Victorian physics, the theories of relativity, astronomy and quantum mechanics, and distinguishing the actual results of modern physics from speculations. The connections with theology are explored throughout. The concluding section draws discussions together and makes an important new contribution to the debate."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Theology, philosophy and physics -- The Judeo-Christian contribution to the development of modern science -- The Muslim centuries -- The Renaissance -- Classical physics -- Space, time and relativity -- Quantum theory -- Quantum mechanics -- Deterministic interpretations of quantum mechanics -- Cosmology -- Chaos and symmetry -- Science and non-Christian religions.
Includes bibliographical references (pages 229-264) and indexes.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Physics -- Religious aspects; Religion and science; Electronic books